DNA Methylation and Immune Cell Markers Demonstrate Evidence of Accelerated Aging in Patients with Chronic Hepatitis B Virus or Hepatitis C Virus, with or without Human Immunodeficienct Virus Co-infection. (11th September 2020) - Gindin, Yevgeniy; Gaggar, Anuj; Lok, Anna S; Janssen, Harry L A; Ferrari, Carlo; Subramanian, G Mani; Jiang, Zhaoshi; Masur, Henry; Emmanuel, Benjamin; Poonia, Bhawna; Kottilil, Shyam
Abstract: Background: Several chronic diseases accelerate biological aging. We investigated age acceleration and the association between peripheral blood DNA methylation (DNAm) and immune cell markers in patients chronically infected with the hepatitis B virus (HBV) or the hepatitis C virus (HCV) with and without human immunodeficiency virus (HIV) co-infection. Methods: Age acceleration was measured as the difference between epigenetic age (Horvath clock) and chronological age. The immune marker model of age acceleration was developed using Elastic Net regression to select both the immune markers and their associated weights in the final linear model. Results: Patients with chronic HBV (n = 51) had a significantly higher median epigenetic age compared to chronological age (age accelerated) ( P  < .001). In patients with chronic HCV infection (n = 63), age acceleration was associated with liver fibrosis as assessed by histology ( P < .05), or presence of HIV co-infection ( P < .05), but not HCV mono-infection. Age acceleration defined by immune markers was concordant with age acceleration by DNA methylation (correlation coefficient = .59 in HBV; P  = .0025). One-year treatment of HBV patients with nucleoside therapy was associated with a modest reduction in age acceleration, as measured using the immune marker model (−.65 years, P  = .018). Conclusion: Our findings suggest that patients with chronic viral hepatitis have accelerated epigenetic aging, that immune markers define biological age, and have the potential to assess the effects of therapeutic intervention on age acceleration. Abstract : We investigated epigenetic aging and its associations with chronic viral hepatitis, liver fibrosis, and immune phenotypes. Age acceleration is associated with chronic hepatitis B virus and chronic hepatitis C virus infection with concomitant human immunodeficiency virus co-infection or liver fibrosis. We present a panel of immune markers that are correlated with epigenetic aging.